Evaluation system waste management: a case study in a public school in the Seridó/RN region - Dantas, Gerbeson Carlos Batista; Barros, Sâmea Valensca Alves; Nazário, Lanna Celly da Silva; Silveira, Arthuro Munay Dantas da; Forbeloni, Jacimara Villar; Pimentel, Patrícia Mendonça (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2022)
This work aims to evaluate the current waste management system employed by a public school in the municipality of Parelhas/RN. It was performed an interview with the school management, followed by observation of waste management steps to understand and quantify management in the period between June-December 2017. The research technique was a systematic and direct intensive observation. According to the inspection, much of the waste is organic, followed by dry, electrical and electronic equipment, construction and demolition, and others. As for management, the packaging of waste is done in plastic containers, partially protected from the weather, with separation of waste. The signage of the containers was adequate, as were the locations in which they were arranged. The leading final destination of the waste is the public management system, however, treatment actions were observed, such as the composting of part of the organic waste for the maintenance of the school garden, the destination of waste to the collector’s association, the reuse of components and the accomplishment of exchanges between public offices. Finally, it was found that the school management system is well-targeted, even if minor adjustments are required